(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Oral squamous cell carcinoma (OSCC) is the most common malignancy in India. Majority of OSCC occurs in relation to various oral potentially malignant disorders (OPMD). Most patients report in advanced stages due to lack of awareness and delay in biopsy. Immunohistochemistry (IHC) could be used to identify the genetic alterations influencing proliferation and apoptosis that accumulate in OPMD and may transform it into OSCC. Bcl2 is one such molecule that enhances cell survival and reduces apoptosis.Aims & Objectives: Our study aimed to determine and compare the expression of Bcl-2 in OPMD and OSCC. Materials and methods: 70 samples were retrieved from the department archives including 10 normal mucosa, 30 cases of OPMD and 30 cases of OSCC. The number of Bcl-2 positive cells was counted in 50 cells of each field by two independent observers. Cases were assigned to one of the following categories: 0% positive cells (-), 10% positive cells (+), 10-25% positive cells (++), 26-50% positive cells (+++) or more than 50% positive cells (++++). They were scored as: 0% positive cells (-), 10% positive cells (+), 10-25% positive cells (++), 26-50% positive cells (+++) or more than 50% positive cells (++++). The data were tabulated and analyzed using CROSSTABS procedures, Mean ± SD, Mann-Whitney’s U-test and Chi Square test using SPSS 15.0 (SPSS INC, Chicago, IL). Results: Mean Bcl-2 expression in 10 Normal Mucosa (N) samples with the Mean values of 0.0824 with the Standard Deviation values of 0.127. In 30 OPMD samples the Mean value was 0.0397 with the Standard Deviation value of 0.083 and in the 30 OSCC samples the Mean value was 0.0301 with the Standard Deviation value of 0.060. Summary: We found increased Bcl2 expression in basal and parabasal cells of normal epithelium but progressive decrease in its expression in OPMD and in OSCC. Though our study did not achieve statistical significance, multi-centre studies on this expression will be helpful to understand the role of this anti-apoptotic molecule.